Physical and mental health complications post-COVID-19: Scoping review - Shanbehzadeh, Sanaz; Tavahomi, Mahnaz; Zanjari, Nasibeh; Ebrahimi-Takamjani, Ismail; Amiri-arimi, Somayeh (Journal of psychosomatic research, 2021)
Several long-lasting health complications have been reported in previous coronavirus infections. Therefore, the aim of this study was to review studies that evaluated physical and mental health problems post-COVID-19. Articles for inclusion in this scoping review were identified by searching the PubMed, Scopus, Web of Science and Google Scholar databases for items dated from 1 January to 7 November 2020. Observational studies evaluating physical health (musculoskeletal symptoms, functional status) or mental health status with a follow-up period longer than 1 month after discharge or after the onset of symptoms were included. This scoping review included 34 studies with follow-up periods of up to 3 months post-COVID-19. The most commonly reported physical health problems were fatigue (range 28% to 87%), pain (myalgia 4.5% to 36%), arthralgia (6.0% to 27%), reduced physical capacity (six-minute walking test range 180 to 561 m), and declines in physical role functioning, usual care and daily activities (reduced in 15% to 54% of patients). Common mental health problems were anxiety (range 6.5% to 63%), depression (4% to 31%) and post-traumatic stress disorder (12.1% to 46.9%). Greater fatigue, pain, anxiety and depression were reported in female patients and individuals admitted to intensive care. An overall lower quality of life was seen up to 3 months post-COVID-19. This review highlights the presence of several physical and mental health problems up to 3 months post-COVID-19. The findings point to the need for comprehensive evaluation and rehabilitation post-COVID-19 to promote quality of life. •Fatigue was the most common musculoskeletal problem post-COVID-19.•Reduced exercise capacity was present post-COVID-19.•Anxiety and depression were the most common mental health problems post-COVID-19.•Physical and mental health problems were prevalent among ICU survivors.•Fatigue and mental health problems were prevalent among women.